2003
DOI: 10.1034/j.1399-6576.2003.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Regionally differentiated fibrinolytic responses during volume‐resuscitated acute endotoxemia in pigs

Abstract: Acute endotoxemia induces a prompt, marked and regionally differentiated pro-fibrinolytic response that cannot be discerned based on systemic levels of circulating tPA and that was normalized during volume resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
2

Year Published

2004
2004
2007
2007

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
2
2
Order By: Relevance
“…In contrast, a previous study in pigs failed to demonstrate that tPA is actively secreted by the pulmonary endothelial cells to yield a positive net pulmonary flux of tPA (2). Pulmonary net release of tPA tended to increase transiently in porcine acute endotoxinemia (3).…”
contrasting
confidence: 69%
See 2 more Smart Citations
“…In contrast, a previous study in pigs failed to demonstrate that tPA is actively secreted by the pulmonary endothelial cells to yield a positive net pulmonary flux of tPA (2). Pulmonary net release of tPA tended to increase transiently in porcine acute endotoxinemia (3).…”
contrasting
confidence: 69%
“…Tissue-type plasminogen activator (tPA) is a key mediator of vascular fibrinolysis to support microvascular patency. Pulmonary net release of tPA tended to increase transiently in porcine acute endotoxinemia (3). In contrast, a previous study in pigs failed to demonstrate that tPA is actively secreted by the pulmonary endothelial cells to yield a positive net pulmonary flux of tPA (2).…”
contrasting
confidence: 67%
See 1 more Smart Citation
“…We have recently demonstrated that acute endotoxemia‐induced circulatory failure in pigs results in increased plasma levels of tPA, and specifically a mesenteric release along with a hepatic uptake of tPA (6). The amount and timing of endotoxin administration, the hemodynamic response and support and the magnitude of the inflammatory response may all have an impact on the fibrinolytic response.…”
mentioning
confidence: 99%